Development Learning Cycle 5E Module Integrated with Science, Technology, Engineering, and Mathematics (STEM) in Thermochemistry - Nirmala Chayati; Mohammad Masykuri; Suryadi Budi Utomo (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
The success of the learning process is something that needs to be considered in 21st-century learning. One of the successes in teaching and learning uses appropriate learning models. One of the 21st-century learning models is the 5E Learning Cycle integrated with Science, Technology, Engineering, and Mathematics (STEM). This learning model encourages student activities in the teaching and learning process, with the encouragement of student activities, students' science process skills will grow. Science process skill is one of skill that student must have in 21st-century learning. One effort to encourage students' process skills is to use a virtual laboratory. This research aims to develop a 5E Learning Cycle module integrated with STEM and is equipped using a virtual laboratory (www.chemcollective.org) on thermochemistry material. This study's subjects were students of class XI of state high schools in the city of Kediri. This research is a Research and Development (R&D). The data collected through interview, observation, and questionnaires. The results of this study are: students need a teaching material that can drive the student achievement of the teaching and learning process in the 21st century in thermochemistry material; module validity which is declared valid by a severe expert (v = 0.89); The module developed shows effective results seen from the learning outcome on thermochemistry material and the module can foster science process skill